Meta-Analysis: The Relationship between Family and School Environments and Social-Emotional Behaviour in Early Childhood - Khasanah, Alfina Fatwa; Maulia, Alfiah; Nuraida, Nuraida; Fidrayani, Fidrayani (Universitas Pendidikan Indonesia Kampus Serang, 2024)
This study aims to analyze the influence of family and school environment interactions on early childhood social-emotional behaviour, considering the importance of emotional intelligence development, which is often overlooked in the current educational context. In many cases, both parents and educational institutions do not maximize programs that focus on this aspect and tend to prioritize increasing intellectual intelligence. The method used in this study is meta-analysis by describing the results of the analysis of various studies that have been published nationally in Indonesia and calculating their effect size. The research sample consisted of 14 articles published in accredited national journals from 2014 to 2024. The instrument employed was a coding sheet containing data and information findings from each article. The findings of the analysis revealed that the average correlation value between family and school environment interactions and early childhood social-emotional behaviour was 0.73, which is included in the high category. This finding confirms that interactions in the family environment significantly influence the development of children's social-emotional behaviour and indicates the need for more attention from schools and parents to integrate emotional intelligence development into the learning process. Thus, this study is expected to provide insight into the importance of the role of families and schools in shaping children's social skills so that they are not only intellectually intelligent but also able to adapt and establish healthy social relationships.